2005
DOI: 10.1111/j.1538-7836.2005.01638.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression studies on a novel type 2B variant of the von Willebrand factor gene (R1308L) characterized by defective collagen binding

Abstract: Summary. A novel mutation, R1308L (3923G > T) was present in the heterozygous state in five members of a family with type 2B von Willebrand disease (VWD) characterized by a full set of von Willebrand factor (VWF) multimers in plasma and by the absence of thrombocytopenia before and after desmopressin (DDAVP). The defect (R1308L) was located at the same amino acid position of one of the most common mutations associated with type 2B VWD (R1308C), which is characterized by the loss of high molecular weight VWF mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
46
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 17 publications
(18 reference statements)
10
46
0
Order By: Relevance
“…During the 24-month follow-up, platelet count were obtained in all the patients both at baseline and during physiologic or pathologic stress conditions all associated with a short-or long-term rise of plasma VWF. Consistent with previous observations, 9,13,14,33 platelet count were highly variable in VWD2B patients. The prevalence of patients with thrombocytopenia was only 30% at baseline but became almost double (58%) when patients were exposed to stress conditions.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…During the 24-month follow-up, platelet count were obtained in all the patients both at baseline and during physiologic or pathologic stress conditions all associated with a short-or long-term rise of plasma VWF. Consistent with previous observations, 9,13,14,33 platelet count were highly variable in VWD2B patients. The prevalence of patients with thrombocytopenia was only 30% at baseline but became almost double (58%) when patients were exposed to stress conditions.…”
Section: Discussionsupporting
confidence: 92%
“…on May 12, 2018. by guest www.bloodjournal.org From P1266L or R1308L mutations 10,33 : we confirmed that none of them developed thrombocytopenia after administration of the drug. This behavior was strictly correlated to genotype because these patients carried 3 mutations only (P1266Q/L or R1308L).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…These findings highlight the importance of interpreting VWF:CB activity in the context of all laboratory and clinical data, as is the case with the other VWF tests. We cannot exclude the possibility, however, that low VWF:CB results, in the absence of multimer pattern abnormalities, could point to isolated abnormalities in the VWF gene sequence at domain 1 and/or 3 containing collagen-binding sites (9 ).…”
Section: © 2006 American Association For Clinical Chemistrymentioning
confidence: 92%